Assessment of clinical outcomes of medicinal cannabis therapy for depression: analysis from the UK Medical Cannabis Registry. (2nd November 2022) - Mangoo, Sajed; Erridge, Simon; Holvey, Carl; Coomber, Ross; Barros, Daniela A Riano; Bhoskar, Urmila; Mwimba, Gracia; Praveen, Kavita; Symeon, Chris; Sachdeva-Mohan, Simmi; Rucker, James J; Sodergren, Mikael H
ABSTRACT: Background: Although pre-clinical experiments associate cannabinoids with reduced depressive symptoms, there is a paucity of clinical evidence. This study aims to analyze the health-related quality of life changes and safety outcomes in patients prescribed cannabis-based medicinal products (CBMPs) for depression. Methods: A series of uncontrolled cases from the UK Medical Cannabis Registry were analyzed. The primary outcomes were changes from baseline in the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), Sleep Quality Scale (SQS), and EQ-5D-5 L at 1, 3, and 6 months. Secondary outcomes included adverse events incidence. Results: 129 patients were identified for inclusion. Median PHQ-9 at baseline was 16.0 (IQR: 9.0–21.0). There were reductions in PHQ-9 at 1-month (median: 8.0; IQR: 4.0–14.0; p < 0.001), 3-months (7.0; 2.3–12.8; p < 0.001), and 6-months (7.0; 2.0–9.5; p < 0.001). Improvements were also observed in GAD-7, SQS, and EQ-5D-5L Index Value at 1, 3, and 6 months (p < 0.050). 153 (118.6%) adverse events were recorded by 14.0% (n = 18) of participants, 87% (n = 133) of which were mild or moderate. Conclusion: CBMP treatment was associated with reductions in depression severity at 1, 3, and 6 months. Limitations of the study design mean that a causal relationship cannot be proven. This analysis provides insights for further study within clinical trial settings. Plain Language Summary: Depression is a highly prevalent mental health condition with approximately one in five people affected by at least one episode of depression in their lifetime. Two cardinal symptoms of depression are low mood and loss of interest. Since depression is such a debilitating condition, improving quality of life is an important part of treatment. Antidepressant medications are currently an important part of treating depression, but the variability in their effectiveness means that there is a need for alternative treatments. Medicinal cannabis, which contains certain chemicals from the cannabis plant, has received growing interest as a potential novel treatment for depression. Due to the lack of clinical studies on the use of medicinal cannabis to treat depression, this study aims to assess the effects of medicinal cannabis on quality of life in patients suffering from depression. The study included 129 patients treated with medicinal cannabis for depression at Sapphire Medical Clinics. The results showed that medicinal cannabis was associated with improvements in depression and anxiety symptoms, as well as health-related quality of life, and sleep quality after 1, 3, and 6 months of treatment. Although there were numerous adverse events in a small number of patients, most of these were mild or moderate. A major limitation is that this study cannot determine the extent to which medicinal cannabis is directly responsible for the improvements in depression symptoms that were observed. Future studies should focus on conducting clinical trials which can better evaluate the true treatment effects of medicinal cannabis for depression.